Strengthening tolerance character and patriotism in elementary school music art learning - Eka Titi Andaryani; Indriana Eko Armaidi; Azzamul Fadhly Noor; Paulus Widjanarko (Jurnal Ilmiah Pendidikan Dasar, 2025)
Tolerance and nationalism are essential components of character education that require focused development during the elementary school years. These values can be effectively cultivated through music education, particularly when aligned with the principles of the Merdeka Belajar (Freedom to Learn) curriculum. This study employs a qualitative descriptive approach utilizing a case study method to explore the integration of character education within the context of music instruction. The findings provide a comprehensive account of the independent learning framework in elementary education and its correlation with music arts pedagogy. Specifically, the study identifies strategies for enhancing students’ tolerance and nationalistic attitudes through music education, as well as the challenges encountered and proposed solutions within this instructional context. The results demonstrate that music education serves as a powerful medium for fostering a sense of tolerance and nationalism among students, thereby reinforcing the development of these core character traits in alignment with the goals of holistic and independent learning.